A Study of LoRa Signal Propagation in Hilly Suburban Area for Smart City Applications - Anzum, Rabeya; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Hakim, Galang P. N. (IEEE, 2021)
Long-range (LoRa) is a wireless LPWAN (Low Power Wide Area Network) communication technology has been developed for many Internet-of-Things (IoT) applications in industrial sectors as well as smart city applications. The performance of LoRa can be affected by environmental factors that was witnessed in recent research trends. Other geological factors like terrain types may also have an impact on the link performance. Hence, this paper highlights the geological factors that affect LoRa performance in hilly area propagation for smart city applications. In addition, an experiment was carried out using 915MHz frequency in the hilly suburban region of Kuala Lumpur, Malaysia to investigate the performance of LoRa utilizing different spreading factors (SF7, SF8, SF10, SF12) and putting the receiver in various altitude scenarios. The RSSI and packet receive ratio (PRR) were used to determine the coverage and performance analysis in hilly suburban area. The outcome of this study shows that the LoRa signal propagation is affected by the hilly terrain scenarios. Because of the hilly region, the coverage could be as limited as 1.25Km and the packet receive ratio was reduced by 65%. Further research is needed to clarify the detailed propagation scenario between the transmitter and receiver in hilly areas to propose an optimal propagation model for a suburban hilly terrain.